Collagen Type I and Type II Expression Evaluation on Cartilage Defect Regeneration Treated with Dwikora–Ferdiansyah–Lesmono–Purwati (DFLP) Scaffold Supplemented with Adipose–Derived Stem Cells (ASCs) or Secretome: An In-Vivo Study - Adrianto Prasetyo Perbowo; Dwikora Novembri Utomo; Lukas Widhiyanto; Primadenny Ariesa Airlangga; Purwati Purwati (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
Abstract Cell-based therapies such as Scaffold, stem cells, and secretome, are one of the alternatives to enhance the regeneration of hyaline-like cartilage in cases of cartilage defects. This study is an in-vivo experiment using animal models, in which we apply a composite of DFLP (Dwikora-Ferdiansyah-Lesmono-Purwati) Scaffold and Adipose-Derived Stem Cells (ASCs) or Secretome to an injury model on the distal femoral trochlea of New Zealand White Rabbits. The animals were divided into four groups: (1) control (K); (2) Scaffold only (S); (3) Scaffold + ASCs (SA); (4) Scaffold + Secretome (SS). Animals were terminated in the 12th week, and an immunohistochemistry (IHC) evaluation for Collagen type I and II were done. Statistical analysis shows that collagen type I IHC between groups shows no significant difference (p = 0.546). Collagen type II IHC shows significant difference between groups (p = 0,016). The findings in this study showed that Scaffold + ASCs group and Scaffold + Secretome have better collagen type II expression compared to the control group. DFLP Scaffold composite with ASCs or Secretome shows potential for cartilage regeneration therapy by increasing type II collagen expression as in hyaline-like cartilage which may be used for regenerative therapy for cartilage defects. Keywords             : DFLP Scaffold; Adipose-Derived Stem Cells (ASCs); Secretome; Collagen Type I; Collagen Type IICorrespondence    : ianperbowo@me.com